The synthesis of thiazolopyrazolo[4,3-d]pyrimidine trihalogenides and anomalies of their NMR spectra - Svalyavin, O.V.; Svalyavin, M.I.; Balya, A.G.; Onis’ko, M.Yu.; Turov, A.V.; Lendel, V.G. (Reports of the National Academy of Sciences of Ukraine, 2014)
By the halogenic cyclization reaction of the thioesters of pyrazolo[4,3-d]pyrimidines, which contains allylic radical or its more complete homologs at the sulfur atom, trihalogenic pyrazolo[3,4-e][1,3]thiazolo[3,2-a]pyrimidine salts have been synthesized. It is discovered that, in the NMR spectra of the obtained compounds, anisochronism of the signals in pairs of ortho- and meta-protons and related carbon atoms of phenyl substituent is observed. The hypothesis is stated that the reason for the observed anomalies of NMR spectra is the magnetically anisotropic action of the anion on the phenyl substituent atoms of the cation.